THE INFLUENCE OF EXPERIENTAL LEARNING ON ELABORATING MINDSET WITH PROACTIVENESS AS A MODERATOR VARIABLE - Irawan, Reita Angela; Dewi, Liliana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to determine the effect of experiential learning on elaborating mindset with proactiveness as a moderator variable. Experiential learning, which refers to learning through direct experience, is believed to improve an individual's ability to think deeply and in a structured way, known as an elaborating mindset. This elaborating mindset is a thinking process that does not only focus on quick solutions, but also considers various perspectives and alternatives before making a decision. However, this influence is not independent. The proactiveness factor, which reflects the level of individual initiative in taking action without direct direction, is believed to play an important role as a moderator variable. In other words, the more proactive a person is, the more significant the impact of experiential learning in developing an elaborating mindset. Through a quantitative approach, data from respondents were analyzed to understand the interaction between the three variables. It is hoped that the results of the study can provide new insights into how learning experiences and levels of proactiveness can encourage a more holistic mindset, especially in the context of more effective decision-making and problem-solving. Keywords: Experiential Learning, Elaborating Mindset, Proactiveness, Moderation Effect, Entrepreneurial Education.